2008
DOI: 10.1007/s00384-008-0458-4
|View full text |Cite
|
Sign up to set email alerts
|

Anti-p53 autoantibody in colorectal cancer: prognostic significance in long-term follow-up

Abstract: Anti-p53 autoantibody is not related to clinical parameters of CRC and has no prognostic significance in long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 15 publications
6
20
0
2
Order By: Relevance
“…Furthermore, Yamaguchi et al (4) reported that other factors, including tumor location, histology, depth of tumor invasion, vessel invasion, distant metastasis, CEA and recurrence, were also significantly associated with positive Ap53Ab expression. Other studies (9,10) reported that no significant correlation was observed between positive Ap53Ab expression and clinicopathological factors. In the present study, several factors, including depth of tumor invasion, lymph node metastasis, stage and CEA, were found to be significantly associated with positive Ap53Ab expression.…”
Section: Ap53ab Expression N (%) -----------------------------------mentioning
confidence: 85%
See 2 more Smart Citations
“…Furthermore, Yamaguchi et al (4) reported that other factors, including tumor location, histology, depth of tumor invasion, vessel invasion, distant metastasis, CEA and recurrence, were also significantly associated with positive Ap53Ab expression. Other studies (9,10) reported that no significant correlation was observed between positive Ap53Ab expression and clinicopathological factors. In the present study, several factors, including depth of tumor invasion, lymph node metastasis, stage and CEA, were found to be significantly associated with positive Ap53Ab expression.…”
Section: Ap53ab Expression N (%) -----------------------------------mentioning
confidence: 85%
“…Although previous reports (8,23) demonstrated that positive Ap53Ab expression was associated with poor prognosis in CRC patients, there appears to be no consensus (4,6,10). Recently, Yamaguchi et al (4) reported that no association between Ap53Ab expression and OS was found in 1384 CRC patients, although Ap53Ab expression was associated with relapse-free survival in 1212 CRC patients who underwent curative surgery.…”
Section: Ap53ab Expression N (%) -----------------------------------mentioning
confidence: 97%
See 1 more Smart Citation
“…p53 Ab levels are elevated in 13-47% of preoperative CRC patients [5,6,7,8,9,10], as well as in patients with other solid tumors, such as in 11.2-32% of gastric cancer patients [12,16,17,18], 13.2-21.5% of breast cancer patients [34,35,36], 8-30% of lung cancer patients [13,19,20,21,22], and 7-32% of hepatocellular carcinoma patients [15,24,25,26,27]. In the present study, the percentage of CRC patients with p53 Ab elevation was 26.3%, corroborating previous reports (table 1).…”
Section: Discussionmentioning
confidence: 99%
“…p53 Ab production is associated with TP53 gene mutation in CRC tissue and the consequent accumulation of mutant TP53 protein. The p53 Ab can be found in 13-47% of CRC patients [5,6,7,8,9,10], and its elevation has been reported in a wide variety of solid cancers such as esophageal, gastric, lung, ovarian, and hepatocellular cancers [11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27]. Thus, the clinical applicability of the p53 Ab in cancer screening is well established.…”
Section: Introductionmentioning
confidence: 99%